JUSTIFICATION OF THE RATIONAL NUMBER OF THE CENTERS OF TRANSPLANTATION IN THE RUSSIAN FEDERATION, THEIR GEOGRAPHY AND NOMENCLATURES - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов)
Aim: to calculate number of the centers of transplantation according to real requirement of the population and a donor resource, to prove their geography and the nomenclature, providing with donor organs. Methods and results. The analysis and comparison of statistical data on population, number of the centers of transplantation, their transplant activity in Russia and abroad are made. Calculation of number of the centers of transplantation is carried out and justification of their geography is offered. The analysis of statistical data on hospitals in the Russia is made, calculation of a rational number of donor hospitals according to need for a donor resource is carried out. Justification of transplant coordination in territorial subjects of the Russia, in federal districts is offered. Justification of the nomenclature of the centers of transplantation and donor hospitals is offered.Conclusion. Settlement data on a rational number of the centers of transplantation, their geography and the nomenclature, providing with the donor organs, suitable developments for planning of the hi-tech medical care in territorial subjects of the Russia are obtained.